A newly isolated Bacillus siamensis SB1001 for mass production of poly-γ-glutamic acid. (May 2020) - Wang, Dexin; Hwang, Jin-Su; Kim, Dong-Ho; Lee, Sungbeom; Kim, Dae-Hyuk; Joe, Min-Ho
Graphical abstract: Highlights: A new γ-PGA producing strain was isolated and identified as B. siamensis. RSM was used to optimize the medium for γ-PGA production. γ-PGA yield of 25.22 g/L was achieved in 24 h in the optimum medium. γ-PGA molecular weight was 7.9 × 10 5 Da with a PDI of 2.34 and a d -glutamate monomer content of 89.71%. Abstract: Poly-γ-glutamic acid (γ-PGA) is a retaining agent; it has applications in the food, medicine, agriculture, cosmetics and wastewater treatment industries. Most of the γ-PGA producing strains belong to the genus Bacillus . This study reports on a novel γ-PGA producing species. Bacillus siamensis SB1001 was screened and isolated from organically cultivated soybeans exhibiting a high γ-PGA producing ability. The fermentation medium and culture parameters for γ-PGA production by Bacillus siamensis SB1001 were optimized by statistical methods. The sucrose, l -glutamic acid and dipotassium phosphate in the medium were shown to be the significant factors of the γ-PGA production, and the optimum medium obtained consisted of the following: 106.86 g/L sucrose, 69.84 g/L l -glutamic acid and 2.39 g/L dipotassium phosphate. Using the optimized medium, 25.22 g/L γ-PGA were produced with a productivity of 1.05 g/L/h. The γ-PGA obtained had a molecular weight of 7.9 × 10 5 Da and a polydispersity index of 2.34, and the ratio of d -/L-glutamic acid was 89.71%:10.29%. To the best of our knowledge, this is the first report of γ-PGA production by B. siamensis strain. B. siamensis SB1001 has great potential as an industrial γ-PGA producer.